Missional ecclesiology as basis for a new church order: A case study - Dreyer, Wim A. (HTS teologiese studies, 2013)
In this contribution the author looks at the ecclesiology and church polity of the Nederduitsch Hervormde Kerk van Afrika (NHKA) as a case study. Different approaches to ecclesiology and church polity by different NHKA theologians are examined. The conclusion is reached that a paradigm shift is required, to assist the church in the process of transformation. Part of the transformation process, is the creation of a church order with a stronger missional orientation. It is argued that, in the context of the 21st century, the missio Dei paradigm and missional ecclesiology could be a suitable point of departure in the creation of a new church order for the NHKA.